Analisis Faktor Penyebab Terjadinya Ketimpangan Kemiskinan pada Kabupaten Pangkep sebagai Upaya Mewujudkan Sustainable Development Goals Pilar tanpa Kemiskinan - abbas, andi bilal (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Pangkajene and Islands Regency (Pangkep) is one of the coastal areas in South Sulawesi that has abundant natural resource potential, but still faces serious challenges in overcoming inequality and high poverty rates. Based on BPS data in 2024, Pangkep was recorded as the district with the highest percentage of poor people in South Sulawesi, at 12.41%. This study aims to analyze the factors that cause poverty and formulate the strategic role of youth in reducing poverty and realizing more equitable and inclusive development in Pangkep. Through a descriptive quantitative approach and interviews with community leaders, it was found that non-inclusive economic growth, limited access to education, unequal distribution of development, and weak local economic empowerment are the main causes of high poverty. Solutions offered include improving the quality of education, empowering MSMEs, financial literacy, developing a tourism sector based on coastal potential, and multi-stakeholder collaboration. Youth as agents of change have a vital role in driving social and economic transformation through digital innovation, active participation in community empowerment, and direct involvement in development programs. With a collaborative and sustainable approach, it is hoped that Pangkep can significantly reduce poverty and become a more ung district.